Disturbed biopterin and folate metabolism in the Qdpr‐deficient mouse. Issue 21 (19th September 2014) - Xu, Feng; Sudo, Yusuke; Sanechika, Sho; Yamashita, Junpei; Shimaguchi, Sho; Honda, Shun-ichiro; Sumi-Ichinose, Chiho; Mori-Kojima, Masayo; Nakata, Rieko; Furuta, Tadaomi; Sakurai, Minoru; Sugimoto, Masahiro; et al.
Abstract : Quinonoid dihydropteridine reductase (QDPR) catalyzes the regeneration of tetrahydrobiopterin (BH4), a cofactor for monoamine synthesis, phenylalanine hydroxylation and nitric oxide production. Here, we produced and analyzed a transgenic Qdpr −/− mouse model. Unexpectedly, the BH4 contents in the Qdpr −/− mice were not decreased and even increased in some tissues, whereas those of the oxidized form dihydrobiopterin (BH2) were significantly increased. We demonstrated that unlike the wild‐type mice, dihydrofolate reductase regenerated BH4 from BH2 in the mutants. Furthermore, we revealed wide alterations in folate‐associated metabolism in the Qdpr −/− mice, which suggests an interconnection between folate and biopterin metabolism in the transgenic mouse model. Abstract : QDPR catalyzes the regeneration of BH4 from quinonoid BH2. The BH4 levels in the Qdpr −/− mice were maintained mainly by the action of DHFR. The Qdpr −/− mice presented wide alterations in folate‐related metabolism. Our data suggest a close metabolic linkage between biopterin and folate.